2009
DOI: 10.2134/jeq2008.0128
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Transport of Antibiotic Residues and Antibiotic Resistance Genes following Land Application of Manure Waste

Abstract: Antibiotics are used in animal livestock production for therapeutic treatment of disease and at subtherapeutic levels for growth promotion and improvement of feed efficiency. It is estimated that approximately 75% of antibiotics are not absorbed by animals and are excreted in waste. Antibiotic resistance selection occurs among gastrointestinal bacteria, which are also excreted in manure and stored in waste holding systems. Land application of animal waste is a common disposal method used in the United States a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
480
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 724 publications
(506 citation statements)
references
References 271 publications
(299 reference statements)
17
480
0
9
Order By: Relevance
“…In addition, heavy metals were also detected in manure-amended soil, which might further enhance the dissemination of antibiotic resistance by co-selection with antibiotics, as observed for copper and zinc [31,32]. Long-term and cumulative inputs of antibiotics and heavy metals and their presence can potentially affect the acquisition and maintenance of ARGs in the environment [11,33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heavy metals were also detected in manure-amended soil, which might further enhance the dissemination of antibiotic resistance by co-selection with antibiotics, as observed for copper and zinc [31,32]. Long-term and cumulative inputs of antibiotics and heavy metals and their presence can potentially affect the acquisition and maintenance of ARGs in the environment [11,33].…”
Section: Discussionmentioning
confidence: 99%
“…After mixing and aging for 24 h (Schlusener et al 2003), the soil samples were extracted with 15 mL of the mixture of acetonitrile and EDTA-McIlvaine buffer (pH 4.0) (2:1) in the presence of ultrasonic treatment, and then (Zorita et al 2009) b (Babić et al 2007) c (Feitosafelizzola and Chiron 2009) d (Park and Choi 2008) e (Sanderson and Thomsen 2009) f (Tolls 2001) g (Lutzhoft et al 1999) h (Diaz-Cruz et al 2006) i (Kan and Petz 2000) j (Jacobsen et al 2004) k l (Kim and Tanaka 2009) m (Calza et al 2009) n (Skinner and Kanfer 1992) p (Chee-Sanford et al 2009) q (Suárez et al 2008) Group Analytes Molecular weight…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Chen et al (2007) identified genes conferring erythromycin (erm) and tetracycline (tet) resistance persisting in swine manure post biofilter treatment. Prior studies have identified elevated levels of antibiotics, antibioticresistant bacteria and antibiotic resistance genes in ground and surface water surrounding confined animal feeding operations (Campagnolo et al, 2002;Chee-Sanford et al, 2009;Heuer et al, 2011). The potential for antibiotics, antibiotic-resistant bacteria and antibiotic-resistance genes leaching into the environment is becoming of greater concern, with approximately 9.2 million hectares of farmland receiving manure annually (Dolliver and Gupta, 2007).…”
Section: Introductionmentioning
confidence: 99%